IMPLEMENTATION OF NON-CASH TRANSACTIONS IN REALIZING TRANSPARENCY, PARTICIPATION AND ACCOUNTABILITY OF FINANCIAL MANAGEMENT AT IAIN SHEIKH NURJATI CIREBON - Saifi, Ani Fatimah Zahra (LPPM STIE Muhammadiah Bandung, 2022)
This study aims to discuss the application of non-cash transactions to realize transparency, participation, and accountability in financial management at IAIN Sheikh Nurjati and what risks may be faced by Iain Sheikh Nurjati Cirebon in implementing this non-cash transaction policy. This study uses a qualitative approach with a descriptive method. The results showed that the implementation of non-cash transactions at IAIN Sheikh Nurjati Cirebon was implemented in 2020 by using the BRI Bank Cash Management System with the same disbursement procedure, only with a non-cash mechanism, namely direct payments ( LS) and stock money (UP) and without supplies ( TUP ). This study also found the risks posed by the application of non-cash transactions at IAIN Sheikh Nurjati, namely the influence of HR competence and the influence of information technology.